Bioleaching as an eco-friendly approach for metal recovery from spent NMC-based lithium-ion batteries at a high pulp density - Roy, Joseph Jegan (2021)
Lithium-ion batteries (LIBs) are extensively used for power storage in most gadgets, electric vehicles (EV), and energy storage devices. Spent LIBs are an excellent source of metals, which can be recycled and reused in new batteries to reduce environmental impacts. Our current study reports bioleaching-mediated metal recovery from spent nickel-, manganese-, cobalt (NMC)-based LIBs at a high solid content, using an autotrophic bacterium Acidithiobacillus ferrooxidans. Inductively coupled plasma-optical emission spectrometry (ICP-OES) analysis showed recoveries of 90% Ni, 92% Mn, 82% Co, and 89% Li from spent LIBs in 72 h at a solid content of 100 g/L. The X-ray diffraction (XRD) and scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX) analyses of the LIB powder before and after bioleaching confirmed that most of the metals leached out from the batteries. A high leaching efficiency was achieved by elevated concentrations of H2SO4 and ferric ion in the A. ferrooxidans culture as well as replenished bacterial culture for three cycles during the bioleaching. The bioleaching process reported here can be used to efficiently extract metals from spent EV batteries in an eco-friendly manner.